Thirteenth international symposium "Prevention of traffic accidents on the road 2016" - Drobnjaković, Aleksandar Ž. (Vojnotehnički glasnik / Military Technical Courier, 2016)
At the symposium, which is considered the most prestigious professional gathering in this area in the Republic of Serbia, members of the Ministry of Defense and the Army of Serbia took a noteworthy part with six expert papers on the security of military participants in road traffic. The Ministry of Defense and the Serbian Armed Forces are making significant efforts to increase the level of security of military participants in traffic, which has an impact on the level of traffic safety in the Republic of Serbia.